Compartmentalized evolution of hepatitis B virus contributes differently to the prognosis of hepatocellular carcinoma. (28th November 2020) - Yin, Jianhua; Chen, Xi; Li, Nan; Han, Xuewen; Liu, Wenbin; Pu, Rui; Wu, Ting; Ding, Yibo; Zhang, Hongwei; Zhao, Jun; Han, Xue; Wang, Hongyang; et al.
Abstract: Serum hepatitis B virus (HBV) mutations can predict hepatocellular carcinoma (HCC) occurrence. We aimed to clarify if HBV evolves synchronously in the sera, adjacent liver and tumors and predict HCC prognosis equally. A total of 203 HBV-positive HCC patients with radical hepatectomy in Shanghai, China, during 2011–15 were enrolled in this prospective study. Quasispecies complexity (QC) in HBV core promoter region was assessed using clone-based sequencing. We performed RNA sequencing on tumors and paired adjacent tissues of another 15 HCC patients and analyzed it with three public data sets containing 127 samples. HBV QC was positively correlated to APOBEC3s' expression level ( r = 0.28, P < 0.001), higher in the adjacent tissues than in the tumors ( P = 6.50e-3), and higher in early tumors than in advanced tumors ( P = 0.039). The evolutionary distance between the sera-derived HBV strains and the tumor-derived ones was significantly longer than that between the sera-derived ones and the adjacent tissue-derived ones ( P < 0.001). Multivariate Cox regression analyses indicated that high HBV QC in the sera predicted an unfavorable overall survival ( P = 0.002) and recurrence-free survival (RFS; P = 0.004) in HCC, whereas, in the tumors, it predicted a favorable RFS ( P < 0.001). APOBECs-related HBV mutations, including G1764A, were more frequent in the sera than in the adjacent tissues. High-frequent A1762T/G1764A in the sera predicted an unfavorable RFS ( P < 0.001), whereas, in the tumors, it predicted a favorable RFS ( P = 0.035). In conclusion, HBV evolves more advanced in the sera than in the tumors. HBV QC and A1762T/G1764A in the sera and tumors have contrary prognostic effects in HCC. Abstract : Hepatitis B virus (HBV) evolves more advanced in the sera than in the tumors of hepatocellular carcinoma (HCC) patients. HBV quasispecies complexity and highly frequent mutations in circulation and tumors have different prognostic effects in HCC. These findings will help in clarifying the inherent regulation of HBV evolution and identifying prognostic markers in HCC.